Epidemiology, prevention methods, and risk factors of foot blisters in French trail ultramarathons - Damoisy, J. B; Destombes, V.; Savina, Y.; Pröpper, C. J.; Braun, C.; Tanné, C. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: Blisters are a common running injury and are known to limit runners` performance. There have been many studies on the subject with contrasting results. It would therefore be useful to describe more clearly blister epidemiology, blister prevention methods, and risk factors of blister development. METHODS: This study is a retrospective anonymous, post-race survey. Runners were contacted by email after races in France during the summer and autumn of 2021 and asked to fill-in an online survey about their experience with blisters and running experiences. RESULTS: Five hundred and thirty-three runners participated, of whom were 468 (88%) men and 47 women (12%), mean age 42±9.75. Sixty-one percent (N.=329) of runners applied blister prevention methods before the start of the race and 29% (N.=155) reported blisters at the end of the race. Most commonly used blisters prevention methods were: anti-friction cream 79% (N.=260), "anti-blister socks" 33% (N.=107), paper tape 13% (N.=44), and topical lemon application 11% (N.=36). Having a history of blisters in the past is strongly associated with blisters onset OR=15.950 (9.135-29.640; P<0.0001). Distances ran between 40 to 74 km appeared to be the less likely to cause blisters OR 0.188 (0.045-0.729; P=0.019). None of the studied blister prevention methods seemed to match the protective effect of running shorter distances. CONCLUSIONS: Having a history of previous blisters is a major risk factor for blister occurrence, while running shorter distances seems protective.